Analysis of Cash Position Effect, Debt to Equity Ratio, Return on Assets, And Loan to Deposit Ratio, Net Call Money Over Pay-out Ratio Dividends (Case Study of Banking Companies Listed on the Indonesia Stock Exchange in 2012 - 2018) - Dwi Ramadani; Sapto Jumono (Journal of Multidisciplinary Academic, 2020)
Dividend policy is the most controversial topic in the context of corporate finance, where the variables that influence it are still uncertain in the literature. Thus, in this study aimed to analyze the effect of cash position, debt to equity ratio, return on assets Loan To Deposit Ratio, and Net Call Money on dividend pay-out ratios, as well as providing information and pictures to investors whose investment objectives are to pursue dividends based on variables. Here, we obtain the observation data form 7 banking companies listed at Indonesia Stock Exchange and actively distributed dividends from 2012 to 2018. The results showed that the variable cash position, debt to equity ratio, and net call money had a positive and significant effect on dividends pay-out ratio, and return on assets, loan to deposit ratio, and a negative and significant effect on the dividend pay-out ratio on data regression.